Mini-review Teknologi Produksi Teh Herbal Gaharu - Wangiyana, I Gde Adi Suryawan; Triandini, I Gusti Agung Ayu Hari (Journal of Agritechnology and Food Processing, 2021)
Agarwood tea is a prospective herbal tea product in the Indonesian marketplace. This product was made from agarwood trees, especially Aquilaria and Gyrinops genera. Agarwood leaves were the primary raw material of agarwood tea products. The leaves processing method into herbal tea products has adopted the conventional tea production method. This method has an essential contribution to maintaining the quality of agarwood tea products. This mini-review emphasizes the importance of systematic procedure and its effect on agarwood tea production technology. Agarwood tea production started with the standardization of raw material preparation. Raw material selection and sterilization were the essential procedure at this stage. Agarwood tea production after raw material preparation involves three steps: drying, chopping, and oxidizing. Dried leaves could produce agarwood tea with more robust characteristics than fresh leaves. Chopping the leaves is essential for agarwood tea product packaging. Oxidizing the leaves could produce agarwood tea with a better tannin concentration. It could be concluded that leaf preparation, drying, chopping, and oxidizing the leaves is an essential processing technology for agarwood leaves to produce a good quality tea.